Pendampingan Kemasan Produk dan Keuangan UMKM - Yogantara, Komang Krishna; Prayogi , Putu Agus (Synergy and Society Service, 2025)
Micro, Small and Medium Enterprises (MSMEs) are one of the government's efforts to improve the welfare and economy of the community. Every year the number of MSMEs increases, but the increase in the number of MSMEs is not accompanied by the understanding and knowledge of the MSME actors themselves, one of which is the MSME in Sudimara Village, Tabanan, Bali. Lack of knowledge about the product packaging process to make it more attractive and financial management are obstacles to the development of MSMEs today. The purpose of this community service is to provide training and assistance on the product packaging process and financial management for MSME members in the village. The method used is learning by doing with a lecture system, discussion and question and answer, as well as bookkeeping practices, packaging making. The service process begins with a visit and seeing directly as an initial survey stage. The next is training and assistance. The result of the last activity is supervision. The result is that the packaging that still uses ordinary plastic now uses plastic, good packaging, and bookkeeping that was previously unrecorded already has its own bookkeeping.